EMOTIONAL INTELLIGENCE AND MENTAL HEALTH AMONG GOVERNMENT AND PRIVATE DOCTORS - Singh, Pratibha (International Journal of Psychosocial Rehabilitation, 2020)
The present study examines the relationship between emotional intelligence and mental health among government and private doctors belonging to Jaunpur and Varanasi headquarters. The sample comprised a hundred medical practitioners, of which 50 were government and 50 were private doctors. The respondents were used by emotional intelligence tests and mental health inventory. It was found that emotional intelligence is highly correlated with mental health. The obtained results show that emotional intelligence is significantly among the respondents and is positively correlated with emotional intelligence and mental health functioning. The finding supported and discussed the relationship between emotional intelligence and mental health.